Black streak discolorations in the heartwood of teak (Tectona grandis) may lead to considerable economic loss. Unfortunately, the actual properties of the discolored wood remain unknown as yet. In this paper, the influence of wood extractives on black streaked heartwood color was evaluated by successive solvent extraction (n-hexane, ethyl acetate, methanol and hot-water) and color measurement (CIELab system). The change in color co-ordinates, difference in brightness (DL*), difference in redness - Ganis LUKMANDARU (Departemen Hasil Hutan, IPB, 2009)
Black streak discolorations in the heartwood of teak (Tectona grandis) may lead to considerable economic loss. Unfortunately, the actual properties of the discolored wood remain unknown as yet. In this paper, the influence of wood extractives on black streaked heartwood color was evaluated by successive solvent extraction (n-hexane, ethyl acetate, methanol and hot-water) and color measurement (CIELab system). The change in color co-ordinates, difference in brightness (DL*), difference in redness (Da*), and difference in yellowness (Db*), between sucessively extracted and control sample was also calculated. Color of black streaked heartwood changed by any solvents, whereas n-hexane and ethyl acetate extractions apparently increased the brightness L* values. Extraction with methanol and hot water slightly affected the color differences. However, some differences were still observed in the color properties between the black streaked and normal heartwood, indicating that some substances are polymeric and tightly bound to the cell wall matrix. Some quinones : tectoquinone, tectol, lapachol, desoxylapachol and its isomer, were detected as major compounds by means of GC-MS in the n-hexane and ethyl acetate soluble extracts. The involvement of those compounds, thus, to the blackening heartwood should be investigated in the future studies. Keywords : Tectona grandis, black streak, color, extractives